Pengajaran Bahasa Inggris pada Siswa SD GMIT 4 Kefamenanu-NTT Menggunakan Bahasa Formula dari Cuplikan Animasi Shrek 2 - Neno, Hesni; Misa, Mikhael (Insan Kreasi Media, 2024)
This activity aims at teaching language formula to students in SD GMIT 4 Kefamenanu-NTT to produce natural language like English native speakers. The teaching method used in this activity is called ABC which stands for Anticipation, Building Knowledge, and Consolidation (Crawford et al, 2005:2). They are three stages which the authors used to teach the students. The formulaic language are taken from a YouTube channel: Learn English with TV Series, episode Shrek 2. The duration of the video is 16.51 minutes. The participants of the activity are 27 students. The result of this activity is the students' enthusiasm for learning English increases and the students' English language skills develop with a more natural use of everyday language.